Some practical translation problems related to the concept of “philological translation” (on the example of the translation of C. Simon’s works from French to Russian) - A. G, Vishnyakov (2020)
The purpose of this paper is to put forward a hypothesis about the “philological translation” of literary texts of increased complexity and test it on the material of specific works. Based on the material of Russian and foreign translation studies, this paper formulates the concept of “philological translation” in the appendix to a specific publishing project within the series “Literary monuments” published by the Institute of World Literature of the Russian Academy of Sciences, and considers the most important practical aspects of the problem of adequate translation of literary texts of increased complexity. The analysis of the translation of two works by the representative of the French New Novel Claude Simon illustrates clearly the example of a “philological translation”. In the course of the study, the authors came to the conclusion that a philological translation implies an appeal to a text that is classical in its richness, complexity, and significance in world literature. The commercial potential of translating such a text is not obvious and requires the publisher to give up short-term profitability, the translator to give up routine work that fits into a predetermined time frame, and the reader to give up focusing on non-problematic (non-conflict, uncomplicated), linear, one-time reading/consumption of the book in favor of re-reading/savoring.